An Analysis of Grammatical Errors in Kpop Tweets - Dinar Faiza; Ade Christanty Yudha Bestari; Meilina Haris Mayekti (Jurnal Sinestesia, 2020)
KPop has fast developing into a global phenomenon almost all over the world. Kpop became a virus that spreads in the world of music and entertainment and even has to be able to compete with western music and rule the world charts. Among other social media, Twitter has received a lot of attention from Kpopers. English plays an important role in communicating among Kpop communities on Twitter. Kpop tweets become effective learning tools to improve English skill of Kpopers. Many of Kpopers use Twitter platform to post their thoughts or comments as well as get information in English. In addition, they also often interact with fellow Kpop fans abroad using English. Based on this phenomenon, this study aims to analyze English language learning in Kpoper’s activities on Twitter, especially in the case of grammatical error in Kpop Tweet. The error analysis determines possible causes of the errors and the implication of the errors committed to language teaching and learning. Findings revealed that most errors were seen within the category of omission of helping verb, subject and punctuation or apostrophe. It was followed by tenses, subject-verb agreement and the use of part of speech and question order on the second until fifth ranks consecutively. The researcher focused more on taking data from Kpoper who use English as EFL (English as a foreign language). It was taken from Kpop Tweets randomly with various topics by screenshooting. Data analysis is carried out with a descriptive qualitative method, focused on finding the nature of the particular event on study.